Economic and Energy Criteria for District Meter Areas Design of Water Distribution Networks - Di Nardo, Armando; Di Natale, Michele; Giudicianni, Carlo; Santonastaso, Giovanni; Tzatchkov, Velitchko; Varela, José (Water (Basel), 2017)
Water Network Partitioning (WNP) improves water network management, simplifying the computation of water budgets and, consequently, allowing the identification and reduction of water losses. It is achieved by inserting flow meters and gate valves into a network which has been previously clustered into subsystems. Generally, the procedures are subdivided into two main steps: the clustering and partitioning phases. At first, network nodes are assigned to each cluster and then the appropriate pipes are selected, in which flow meters or gate valves are to be inserted. In this paper, an improved multilevel-recursive bisection algorithm was used to achieve network clustering. To better allocate the hydraulic devices, the partitioning phase was carried out through the minimization of a novel, multi-objective function, taking simultaneous account of energy and economic aspects. The aim is to define a solution that occupies a minimum possible number of flow meters, simplifying the water budget computation, preserving the hydraulic performances, and minimizing the capital and the operational costs. The procedure was tested on an extensive and real Mexican network, providing different optimal solutions and a smart Decision Support System (DSS) (based on visual diagrams and innovative energy, robustness, and balancing metrics).